Recent brachiopods from the southern Brazilian shelf: Palaeontological and biogeographical implications - Simoes, M. G.; Kowalewski, M.; Mello, LHC; Rodland, D. L.; Carroll, M. (Blackwell Publishing, 2004)
Until recently, the rhynchonelliform (articulated) brachiopod fauna from the Brazilian continental shelf (western South Atlantic) was represented only by the endemic species Bouchardia rosea (Mawe), reported from coastal waters of the states of São Paulo and Rio de Janeiro. The present study, based on samples from coastal (<30 m), shelf, and continental slope waters (99-485 m), documents the South Atlantic brachiopod fauna and shows that this fauna is more widespread, diverse, and cosmopolitan than previously thought. Based on a total of 16,177 specimens, the following brachiopods have been identified: Bouchardia rosea (Family Bouchardiidae), Platidia anomioides (Family Platidiidae), Argyrotheca cf. cuneata (Family Megathyrididae), and Terebratulina sp. (Family Cancellothyrididae). In coastal settings, the fauna is overwhelmingly dominated by Bouchardia rosea. Rare juvenile (<2 mm) specimens of Argyrotheca cf. cuneata were also found at two shallow-water sites. In shelf settings (100-200 m), the fauna is more diverse and includes Bouchardia rosea, Terebratulina sp., Argyrotheca cf. cuneata, and Platidia anomioides. Notably, Bouchardia rosea was found in waters as deep as 485 m, extending the known bathymetric range of this genus. Also, the record of this brachiopod in waters of the state of Parana is the southernmost known occurrence of this species. The genera Platidia and Terebratulina are documented here for the first time for the western South Atlantic. The Brazilian brachiopod fauna shares similarities with those from the Atlantic and Indian shelves of southern Africa, and from the Antarctic, Caribbean and Mediterranean waters. The present-day brachiopods of the western South Atlantic are much more cosmopolitan than previously thought and their Cenozoic palaeobiogeographic history has to be reconsidered from that perspective.
Keywords: Terebratulida; recent; south-east Brazilian bight